Contextualizing assessment feedback in translation education: A corpus-assisted ecological approach - Man, Deliang; Zhu, Chenghao; Chau, Meng Huat; Maruthai, Elanttamil (Frontiers in Psychology, 2022)
Despite its powerful influence on student learning, assessment feedback has received relatively less attention in translation education. The mainstream assessment practices in translation education have relied mainly on a static approach to translation competence. The consequences of a static approach include a partial representation of translation competence development and a deficit view of students and their learning. Alternatively, this paper argues for an ecological approach to contextualize assessment feedback in translation education. The ecological approach emphasizes the spatial and temporal context for translation assessment. While detailed contextual information is essential to the ecological assessment approach, assessing translation performance across tasks and time is a considerable challenge. In response to such a challenge, this conceptual paper proposes a corpus-assisted approach to translation assessment. It discusses how a longitudinal student translation corpus can be developed to assist ecological assessment feedback on translation performance. A project in progress based on a translation education program is reported as a case in point for illustrative purposes. The paper has suggested ways forward for future assessment feedback practice and research in translation education.